1991
DOI: 10.1073/pnas.88.18.8222
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin gene transcription is regulated by iron in soybean cell cultures.

Abstract: Iron-regulated ferritin synthesis in animals is dominated by translational control of stored mRNA; ironinduced transcription of ferritin genes, when it occurs, changes the subunit composition of ferritin mRNA and protein and is coupled to translational control. Ferritins in plants and animals have evolved from a common progenitor, based on the simi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
164
1
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(179 citation statements)
references
References 51 publications
8
164
1
5
Order By: Relevance
“…In line with this, ferritin mRNAs are also strongly accumulated in response to iron overload in vascular plants (Arnaud et al, 2006;Lescure et al, 1991;Petit et al, 2001b).…”
Section: Discussionmentioning
confidence: 50%
“…In line with this, ferritin mRNAs are also strongly accumulated in response to iron overload in vascular plants (Arnaud et al, 2006;Lescure et al, 1991;Petit et al, 2001b).…”
Section: Discussionmentioning
confidence: 50%
“…It has been demonstrated that ferritin plays a crucial role in iron storage in higher plants [35][36][37] and unicellular microalgae. 19,[38][39][40] On the other hand, ferritin contribution to iron storage in macroalgae or seaweeds is explored only recently, 24) although a ferritin gene is described as a stress-induced gene in a green seaweed Ulva sp.…”
Section: Unpublished Data)mentioning
confidence: 99%
“…In contrast, PCs are a family of enzymatically synthesized Cys-rich peptides. The induction of PC synthesis is based on the posttranscriptional activation of preformed PC synthase and is not under transcriptional control.Several heavy metal-inducible genes have been reported in plants (Hagen et al, 1988;Lescure et al, 1991;Berna and Bernier, 1999), but surprisingly, little is known about the transcriptional regulation of gene expression in response to heavy metals. In particular, the cis-acting elements conferring heavy metal responsiveness are poorly characterized, and heavy metalspecific responsive promoters have not yet been reported in higher plants.…”
mentioning
confidence: 99%